Unobserved heterogeneous effects in the cost efficiency analysis of electricity distribution systems - Per J. Agrell; Mehdi Farsi; Massimo Filippini; Martin Koller (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
The purpose of this study is to analyze the cost efficiency of electricity distribution systems in order to enable regulatory authorities to establish price- or revenue cap regulation regimes. The increasing use of efficiency analysis in the last decades has raised serious concerns among regulators and companies regarding the reliability of efficiency estimates. One important dimension affecting the reliability is the presence of unobserved factors. Since these factors are treated differently in various models, the resulting estimates can vary across methods. Therefore, we decompose the benchmarking process into two steps. In the first step, we identify classes of similar companies with comparable network and structural characteristics using a latent class cost model. We obtain cost best practice within each class in the second step, based on deterministic and stochastic cost frontier models. The results of this analysis show that the decomposition of the benchmarking process into two steps has reduced unobserved heterogeneity within classes and, hence, reduced the unexplained variance previously claimed as inefficiency.
Keywords: L92; L50; L25; 330; Efficiency analysis; cost function; electricity sector; incentive regulation; Elektrizitätswirtschaft; Regulierung; Kosten-Nutzen-Analyse; Kostenfunktion; Effizienzmarkthypothese